Electrically tunable on-chip quantum Deutsch-Jozsa algorithm with lithium niobate metasurfaces - Li, Haoyu; Yang, Ruisheng; Zhang, Yinan; Dou, Linyuan; Luo, Yijie; Liang, Haigang; Fan, Yuancheng; Wei, Zeyong (RSC advances, 2024)
Owing to the inherent advantages of parallelism, rapid processing speed, and minimal energy consumption, optical analog computing has witnessed a progressive development. Quantum optical computing exceeds the capabilities of classical computing in terms of computational speed in numerous tasks. However, existing metamaterial-based quantum Deutsch-Jozsa (DJ) algorithm devices have large structural dimensions and are not suitable for miniaturized optical computing systems. Furthermore, most reported on-chip metasurface devices, rendered monofunctional after fabrication, do not possess sophisticated optical systems. In this work, we develop an electrically tunable on-chip DJ algorithm device on a lithium-niobate-on-insulator (LNOI) platform. The on-chip device consists of various etched slots, each with carefully designed size. By applying different external voltages to each individual unit, precise phase redistribution across the device is attainable, enabling the realization of tunable DJ algorithm. Notably, we can determine whether the oracle metasurface yields a constant or balance function by measuring the output electric field. The on-chip device is miniaturized and easy to integrate while enabling functional reconfiguration, which paves the way for numerous applications in optical computing. An on-chip quantum Deutsch-Jozsa algorithm device enables electrical tuning by applying varying external voltages to each unit via two gates.